A Symbolic Simulator Platform for the Static Analysis of Thin Plates - Costa, Diogo M.S.; Bernardo, Gonçalo M.S.; Loja, Maria A.R. (International Journal of Online and Biomedical Engineering (iJOE), 2016)
The integration of symbolic capabilities into a simulation platform devoted to the analysis of thin plates can provide a greater flexibility in the learning process as it enables to incorporate, to experiment and simulate more complex and user-defined characteristics. With the present work one has built a symbolic simulator for the study of the mechanical behavior of thin plates. These plates, with a rectangular/square basis geometric configuration, are simply supported along its four edges, and can be made from homogeneous or non-homogeneous materials. The capabilities of this platform are briefly illustrated through an illustrative case study.